2009
DOI: 10.1016/j.clim.2009.07.010
|View full text |Cite
|
Sign up to set email alerts
|

Cutaneous lymphocyte-associated antigen (CLA) T cells up-regulate P-selectin ligand expression upon their activation

Abstract: Memory T cells expressing CLA occur in humans and accumulate in normal and inflamed skin. These cells uniformly bind to the vascular adhesion molecule E-selectin, yet only a subset bind to P-selectin. The latter cells are distinguished by the mAb CHO-131, and are enriched in psoriasis lesions. Activated T cells up-regulate CLA expression, but little is currently known about their binding to P-selectin. We observed that CLA + CD4 + T cells derived from stimulated naïve T cells uniformly express the CHO-131 epit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
6
0

Year Published

2012
2012
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(6 citation statements)
references
References 48 publications
0
6
0
Order By: Relevance
“…This fact, together with the finding that T cell inflammatory reactions are important regulators of lymphedema, suggests that the expression of skin homing receptors may also play an important role in the development of lymphedema. This hypothesis is supported by the finding that the expression of CLA ligand E-selectin ( 74 ) as well as other leukocyte adhesion molecules (ICAM1, VCAM1) is significantly increased in lymphedematous skin ( 60 ). Similarly, we have found that the expression of ligands for CCR4 [chemokine c-c motif ligand 17 (CCL17)] and CCR10 (CCL27) ( 75 ) is markedly increased in keratinocytes of lymphedematous skin.…”
Section: Lymphedema Results In a Mixed T Helper Cell Differentiation mentioning
confidence: 84%
“…This fact, together with the finding that T cell inflammatory reactions are important regulators of lymphedema, suggests that the expression of skin homing receptors may also play an important role in the development of lymphedema. This hypothesis is supported by the finding that the expression of CLA ligand E-selectin ( 74 ) as well as other leukocyte adhesion molecules (ICAM1, VCAM1) is significantly increased in lymphedematous skin ( 60 ). Similarly, we have found that the expression of ligands for CCR4 [chemokine c-c motif ligand 17 (CCL17)] and CCR10 (CCL27) ( 75 ) is markedly increased in keratinocytes of lymphedematous skin.…”
Section: Lymphedema Results In a Mixed T Helper Cell Differentiation mentioning
confidence: 84%
“…Furthermore, PSGL-1 can be modified via a carbohydrate epitope through fucosyltransferase VII activity into the cutaneous lymphocyte-associated antigen (CLA) that regulates tissue-specific homing of memory T cells [106]. Resident T cells in the lung and skin express high levels of PSGL-1, but only those in the skin are CLA + [105108]. In contrast, effector memory cells can engage P-selectin to migrate into lymph nodes undergoing a response [26].…”
Section: Functions Of Psgl-1 In T Cellsmentioning
confidence: 99%
“…A decrease in the level of lymphocytes in group C animals may be due to their release from the circulation for the implementation of regulatory protective functions directly in the endothelial tissues, as well as, possibly, in the underlying connective tissue and peripheral immune organs. In particular, it is known that up to 15% of circulating blood cells are CLA-positive T-lymphocytes associated with the cutaneous lymphocyte antigen CLA, which is considered a receptor that controls the affinity of T-lymphocytes for the skin ( Ni and Walcheck, 2009 , De Jesús-Gil et al, 2018 ). It can be assumed that the investigated biomolecules, on the one hand, send CLA-positive T-lymphocytes from the bloodstream to the inflammation focus, and on the other hand, increase the functional activity of lymphocytes and other leukocytes remaining in the blood.…”
Section: Discussionmentioning
confidence: 99%